ON THE CONNECTIVITY OF PHYSICS AND MATHEMATICS IN HIGH SCHOOL EDUCATION - Dehqonova, Ohista; Urazov, Abdixoliq; Mamatmuradova , Mohigul; Mamatmuradova , Mohigul (Физико-технологического образование, 2021)
The question aboun connectivity physics and mathematics in the educational system is investigated. It was shown that interdisciplinary integration is presented as a means of increasing students’ independent creative abilities, increasing and shaping their worldview and scientific thinking, and ultimately improving the entire educational process